Emotional Facial Expression Based On Action Units and Facial Muscle - Ahmad Hoirul Basori; Hani Moaiteq Abdullah AlJahdali (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The virtual human play vital roles in virtual reality and game. The process of Enriching the virtual human through their expression is one of the aspect that most researcher studied and improved. This study aims to demonstrate the combination of facial action units (FACS) and facial muscle to produce a realistic facial expression. The result of experiment succeed on producing particular expression such as anger, happy, sad which are able to convey the emotional state of the virtual human. This achievement is believed to bring full mental immersion towards virtual human and audience. The future works will able to generate a complex virtual human expression that combine physical factos such as wrinkle, fluid dynamics for tears or sweating.